Proposed framework for evaluating the safety of dietary supplements : for comment (National Academy Press, 2002)
This report outlines a three-step framework for considering the safety of dietary supplement ingredients. The first two steps in the process, "screening/flagging" and "priority setting," are designed to categorize dietary supplement ingredients based on theoretical or possible concern, and therefore the immediacy of the need for in-depth evaluation of safety, the third step of the process.